PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI FORQUE DEPOK - Rizky Ardhana; Darwin Raja Unggul Saragih (LPPM Universitas Asa Indonesia, 2023)
The purpose of this study is to determine product quality, price perception and location in improving purchasing decisions in Forque Depok. This research uses a quantitative approach in the form of a survey, with 100 customers and 30 respondents tested for validity and reliability. Purposive sampling is used to identify respondents by distributing questionnaires to customers who have made minimal visits. Instrument measurements with Likert scale refer to variables and research indicators. Research findings show that product quality has a positive and significant effect on purchasing decisions, the same thing happens with price perception. However, the location variable has no effect on the purchase decision variable. These results also show that a combination of three variables significantly influences purchasing decisions.